One-Visit Versus Two-Visit Root Canal Treatment: Effectiveness in the Removal of Endotoxins and Cultivable Bacteria - Xavier, Ana Claudia C. [UNESP]; Martinho, Frederico C. [UNESP]; Chung, Adriana [UNESP]; Oliveira, Luciane D. [UNESP]; Jorge, Antonio O. C. [UNESP]; Valera, Marcia C. [UNESP]; Carvalho, Claudio A. T. [UNESP] (Elsevier B.V., 2013)
Introduction: This clinical study was conducted to compare the effectiveness of 1-visit versus 2-visit root canal treatment in removing endotoxins and cultivable bacteria from primarily infected root canals. Methods: Forty-eight primarily infected root canals were selected and randomly divided into 4 groups: G1, 1% NaOCl; G2, 2% chlorhexidine (CHX) gel; 63, 1% NaOCl + Ca(OH)(2); and G4, 2% CHX gel + Ca(OH)(2) (all, n = 12). G1 and G2 involved 1-visit treatment, whereas G3 and 64 involved 2-visit treatment with the placement of Ca(OH)(2) medication for 14 days. Samples were collected before and after root canal procedures. A chromogenic LAL assay test was used to quantify endotoxins. Culture techniques were used to determine bacterial counts. Results: Endotoxins and cultivable bacteria were detected in 100% of the initial samples. All treatment protocols were effective in reducing bacterial load from infected root canals: G1 (1% NaOCl, 99.97%), G2 (2% CHX gel, 99.75%), G3 (1% NaOCl + Ca(OH)(2), 99.90%), and 64 (2% CHX gel + Ca(OH)(2), 96.81%), respectively (P < .05). No differences were found in bacterial load reduction when comparing 1-visit and 2-visit treatment groups, irrespective of the irrigant tested (P > .05). Higher median percentage values of endotoxin reduction were achieved in the 2-visit treatment groups (G3, 98.01% and 64, 96.81%) compared with 1-visit treatment groups (G1, 86.33% and G2, 84.77%) (all P < .05). Conclusions: Both 1-Visit and 2-visit root canal treatment protocols were effective in reducing bacteria and endotoxins, but they were not able to eliminate them in all root canals analyzed. Furthermore, 2-visit root canal treatment protocols were more effective in reducing endotoxins than 1-visit root canal treatment protocols.
Keywords: Endotoxin; LAL; limulus amebocyte lysate assay; root canal